Download presentation

Presentation is loading. Please wait.

Published byAlexis Edwards Modified over 2 years ago

1
15-Feb-14Created by Mr. Factors Factors Example :Find the factors of 56. F56 =1 and 56 2 and 28 S3 Credit Numbers that divide into 56 without leaving a remainder 4 and 14 7 and 8

2
Factors 15-Feb-14Created by Mr. Highest Common Factor We need to write out all factor pairs in order to find the Highest Common Factor. Highest Common Factor Largest Same Number S3 Credit

3
F8 =1 and Factors 15-Feb-14Created by Mr. Example :Find the HCF of 8 and 12. HCF = 4 F12 = 1 and 12 2 and Highest Common Factor S3 Credit

4
2 and 5x F4x =1, and 4x Factors 15-Feb-14Created by Mr. Example :Find the HCF of 4x and x 2. HCF = x Fx 2 = 1 and x2x2 Highest Common Factor F5 = 1 and 5 Example :Find the HCF of 5 and 10x. HCF = 5 F10x = 1, and 10x S3 Credit 5 and 2x 10 and x 2 and 2x 4 and x x and x

5
F ab =1 and ab a and b Factors 15-Feb-14Created by Mr. Example :Find the HCF of ab and 2b. HCF = b F2b = 1 and 2b 2 and b Highest Common Factor F 2h 2 = 1 and 2h 2 2 and h2 h2, h 2h Example :Find the HCF of 2h 2 and 4h. HCF = 2h F4h = 1 and 4h 2 and 2h 4 and h S3 Credit

6
15-Feb-14Created by Mr. Factors Find the HCF for these terms (a)16w and 24w (b) 9y 2 and 6y (c) 4h and 12h 2 (d)ab 2 and a 2 b 8w 3y 4h ab S3 Credit

7
15-Feb-14Created by Mr. Factorising Example Factorise 3x Find the HCF for 3x and HCF goes outside the bracket3( ) 3.To see what goes inside the bracket divide each term by HCF 3x ÷ 3 = x15 ÷ 3 = 53( x + 5 ) Check by multiplying out the bracket to get back to where you started S3 Credit

8
15-Feb-14Created by Mr. Factorising Example 1.Find the HCF for 4x 2 and 6xy2x 2.HCF goes outside the bracket2x( ) 3.To see what goes inside the bracket divide each term by HCF 4x 2 ÷ 2x =2x6xy ÷ 2x = 3y2x( 2x- 3y ) Factorise 4x 2 – 6xy Check by multiplying out the bracket to get back to where you started S3 Credit

9
15-Feb-14Created by Mr. Factorising Factorise the following : (a)3x + 6 (b) 4xy – 2x (c) 6a + 7a 2 (d)y 2 - y 3(x + 2) 2x(2y – 1) a(6 + 7a) y(y – 1) Be careful ! S3 Credit

Similar presentations

© 2016 SlidePlayer.com Inc.

All rights reserved.

Ads by Google